Many plants naturalized as aliens abroad have also become more common within their native regions - Paudel, Rashmi; Fristoe, Trevor S; Kinlock, Nicole L; Davis, Amy J S; Zhao, Weihan; Van Calster, Hans; Chytrý, Milan; Danihelka, Jiří; Decocq, Guillaume; Ehrendorfer-Schratt, Luise; Guo, Kun; Guo, Wen-Yong; et al. (Nature communications, 2025)
Due to anthropogenic pressure some species have declined whereas others have increased within their native ranges. Simultaneously, many species introduced by humans have established self-sustaining populations elsewhere (i.e. have become naturalized aliens). Previous studies have shown that particularly plant species that are common within their native range have become naturalized elsewhere. However, how changes in native distributions correlate with naturalization elsewhere is unknown. We compare data on grid-cell occupancy of native vascular plant species over time for 10 European regions (countries or parts thereof). For nine regions, both early occupancy and occupancy change correlate positively with global naturalization success (quantified as naturalization in any administrative region and as the number of such regions). In other words, many plant species spreading globally as naturalized aliens are also expanding within their native regions. This implies that integrating data on native occupancy dynamics in invasion risk assessments might help prevent new invasions.
Keywords: rostliny; Plants; ekosystém; Evropa; Europe; zavlečené druhy; lidé; Ecosystem; Humans; Introduced Species